Kontribusi Pekerja Wanita dalam Meningkatkan Kesejahteraan Keluarga dan Proses Pengambilan Keputusan dalam Keluarga - Rudy Catur Rohman Kusmayadi (Iqtishodia: Jurnal Ekonomi Syariah, 2017)
Woman role for a family in this decade is really controversial and debatable which attract many interest especially related with gender issue. Thus, government launch regulation RI No 23 year 2004 about decision of abandoning any violence in a family that related with rule no 3 point b about gender equality. Woman equality proposes woman and man have equal status and condition to gain human right fully, potential and life of family proportionally. In accordance with the previous case, the more woman work to help their husband for improving family prosperity. Besides, need and demand of life grows high which encourage woman to work outside their house. This case is supported by global economic condition especially for the main need of family which days by days the price is growing higher. Concerning on those concepts, the more woman who work to help their husband for improving family prosperity since need and demand in family grows high. In addition, in a family, woman is demanded to be able manage money well in relation with economic condition which is still unstable because the salary of husband cannot afford need and demand of family. Keyword: gender equality, woman worker, decision taker.